Career interests of a sample of administrators in Chile - Raineri Bernain, Andrés (Estudios de Administración, 1998)
This research explores the career interests of Chilean managers and professionals. The most important determinants of career development are discussed. The role of career interests in this process is commented. A manager’s career interest clasification developed by Schein (1978) was used to measure the career interests of a sample of local managers. General tendencies of the sample and the distribution of preferences for different types of career interests are discussed. Finally, a cluster analysis is performed of the data, in order to identify the profiles of career interests that better describe the sample of Chilean managers. These analyses show that five categories of career interest profiles can be identified in the sample. The relevance of these findings is discussed and career development suggestions are made for the different groups of people behind each profile.